EFFECTS OF STOCKING DENSITY AND WATER DEPTH ON GROWTH AND SURVIVAL OF FRESHWATER CATFISH (CLARIAS MACROCEPHALUS GUNTHER) LARVAE - Mollah, M F A (Indian Journal of Fisheries, 2011)
Five-day old Clarias macrocephaliis larvae of initial total length7.9 + 0.4 mm, when reared at a stocking density of 2 fish 1"' for 28 days,attained significantly larger size compared to those at stocking densities of 4, 8and 16 fish 1-' in water depth of either 4, 8 or 12 cm. A water depth of 4 cmwas suitable for the larvae raised at all the stockiing densities until day 14.During day 14-28 of culture, a stocking density up to 8 fish !-' is recommendedprovided the water depth is maintained within 12 cm.